Constructionism in non-goal orientated virtual worlds - Girvan, Carina (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2013)
Non-goal orientated virtual worlds have gained particular interest from educators in recent years; however learning experiences tend to replicate traditional praxis and lack pedagogical underpinning. This thesis proposes that to move from replication towards innovation, learning experiences need to be underpinned by pedagogical theory which can leverage the unique combination of perceived educational affordances of the technology.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin.